Pengaruh Beban Kerja dan Konflik Pekerjaan Keluarga terhadap Kinerja Karyawan dengan Stres Kerja sebagai Variabel Intervening pada PT Bank BRI (Persero) Tbk. Cabang Panakkukang Makassar - MALIHA, ULY (Study of Scientific and Behavioral Management, 2024)
The objectives of this research are: 1) To determine the effect of workload on work stress. 2) To determine the effect of work-family conflict on work stress. 3) To determine the effect of workload on employee performance. 4) To determine the effect of work-family conflict on employee performance. 5) To determine the effect of work stress on employee performance. 6) To determine the effect of workload on employee performance through work stress. 7) To determine the effect of work-family conflict on employee performance through work stress. This research is a type of quantitative research and the research sample is 105 employees of Pt. Bank BRI (Persero) Tbk Panakkukang Makassar Branch. This research uses path analysis for data analysis with the help of the SPSS version 25 program. The results of the research show that 1) Workload has a positive and significant effect on work stress. 2) Work-family conflict has a positive and significant effect on work stress. 3). Workload has a positive and significant effect on employee performance. 4) Work-family conflict has a positive and significant effect on employee performance. 5) Work stress has a negative and significant effect on employee performance. 6) Workload has a positive and significant effect on employee performance but cannot be mediated by work stress. 7) Work-family conflict has a positive and significant effect on employee performance which is mediated by work stress.